Journalism in the Age of Digital Technology - Srivastava, Dr.Manish Kumar; Sharma, Ms. Gunjan (IJRDO- Journal of Educational Research, 2016)
The information age has created many challenges for every profession. In the case of journalismthe introduction of information technology has altered considerably various aspects of theprofession. The high tech revolution has significantly altered the way the public obtains its newsand information, and has deprived the mass media of its traditional monopoly. This paper willexplore intersections between new media, journalism and technology in order to enhance ourunderstanding of the influence of information and communication technology, especially internettechnology on traditional journalism. The media and the practice of journalism, however, havebeen slow to adjust to the Internet and the global ramifications produced by the new informationtechnology. In the past decades, journalists in the Western World have benefited from thetremendous growth in information communication technologies – ICTs – and in the last ten yearsthe ICTs have also penetrated the developing world and have made available computers, Internetaccess, and mobile technology. This development has probably eased journalistic workingprocedures in these parts of the world. Though journalists throughout the world still separate“domestic” from “foreign,” while their audiences casually chat between continents.Today various computerized sources are regularly being used in media organizations. This paperinvestigates the adoption of information technology, three broad themes reflecting the role of themedia in the digital age emerged from the Journalism, how journalists use these new tools toadvance their profession, write for global audience and news gathering, the role of Internet; whatthe security and ethical implications are in this new realm; and whether freedom of the pressnecessarily means freedom of access, confusion created by new digital technologies and thepower, speed and usefulness of digital creation, transmission and reception.This paper also considers that while the new digital platforms and technologies do presentsignificant challenges to traditional journalism, they are also enabling technologies that offeropportunities to reinvigorate newsgathering. Although the future of journalism is a digital one,the core competencies of a good journalist will be as important as ever.